Alan Fincham and the era of enamel protein Biochemistry - Diekwisch, Thomas G. H. (Frontiers in Physiology, 2022)
Enamel research experienced an unprecedented period of growth during the latter part of the 20th century until today. This growth is in part due to the contributions of a number of iconic scientists such as Alan G. Fincham, the focus of the present review. Alan was involved in many of the seminal discoveries of this time, including the identification of the critical amelogenin peptides TRAP and LRAP, the determination of the amelogenin amino acid sequence, and the amelogenin nanosphere theory. Alan was also a superb mentor of graduate students and colleagues. His experience and leadership related to problem-based learning greatly affected predoctoral dental education at the University of Southern California and in the United States.